2022
DOI: 10.3389/fpsyt.2022.912697
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Ictal Changes in Depression and Anxiety in Persons With Epileptic and Non-epileptic Seizures

Abstract: ObjectiveWe tested the hypothesis that epileptic, but not non-epileptic, seizures would produce an improvement in comorbid depression and anxiety symptoms in the peri-ictal period, much like the antidepressant effects of electroconvulsive therapy.MethodsWe examined depression and anxiety symptoms in patients admitted to an inpatient unit for continuous video electroencephalography as part of routine clinical care. Patients completed three questionnaires that included the Beck Depression Inventory-II (BDI), Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…A study by Gargiulo et al [28] comparing the levels of perceived stress, resilience, and stress-coping levels and the relationship with psychiatric symptoms to identify psychopathological patterns in patients with PNES, drug resistant epilepsy (DRE) and controls identified higher levels of perceived stress with lower levels of resilience in the PNES cohort than the controls. Hopp et al [29] observed that seizures produce a significant improvement in mood scores within a 24-h period in patients with both ES or PNES. The improvement in mood after seizures appeared transient and depression and anxiety scores trended back toward the baseline when assessed 2 weeks after the seizure.…”
Section: Psychological Underpinningsmentioning
confidence: 99%
“…A study by Gargiulo et al [28] comparing the levels of perceived stress, resilience, and stress-coping levels and the relationship with psychiatric symptoms to identify psychopathological patterns in patients with PNES, drug resistant epilepsy (DRE) and controls identified higher levels of perceived stress with lower levels of resilience in the PNES cohort than the controls. Hopp et al [29] observed that seizures produce a significant improvement in mood scores within a 24-h period in patients with both ES or PNES. The improvement in mood after seizures appeared transient and depression and anxiety scores trended back toward the baseline when assessed 2 weeks after the seizure.…”
Section: Psychological Underpinningsmentioning
confidence: 99%